SUBSTITUTION METHOD IN INTEGRATION

In this page substitution method in integration we are going see where we need to use this method in integration. In this method we need to change the function which is defined one variable to another variable. If we have limits then we have to change that too.

Now let us see some example problems to understand this topic.

Problem 1 :

Integrate cos x/(1+sin x)

Solution :

=  ∫[cos x/(1 + sin x)] dx

Let U = 1+sin x

Differentiate with respect to x on both sides

du  =  cos x dx

∫ [cos x/(1+sin x)] dx  =  ∫ [cos x dx/(1+sin x)]

=  ∫ du/u

=  ∫ (1/u) du

=  log u + C

=  log (1+sin x) + C

Problem 2 :

Integrate (6x + 5)/√(3x2+5x+6)

Solution :

=  ∫ [(6x + 5)/√(3x²+5x+6)] dx

Let U = 3x2 + 5x + 6

Differentiate with respect to x on both sides

du = (6x+5) dx

=  ∫ (6x+5) dx/√(3x2+5x+6)

=  ∫du/√u

=  ∫ u^(-1/2) du

=  u^[(-1/2) + 1]/[(-1/2) + 1] + C

=  u^[(-1 + 2)/2]/[(-1 + 2)/2] + C

=  u^(1/2)/(1/2) + C

=  2 √u + C

=  2 √(3x2+5x+6) + C

Problem 3 :

Integrate cosec x

Solution :

=  ∫ cosec x dx

To solve this problem we have to multiply and divide by (cosec x - cot x)

=  ∫ cosec x (cosec x - cot x)/(cosec x - cot x) dx

Let U = (cosec x - cot x)

Differentiate with respect to x on both sides

du = - cosec x cot x - (- cosec² x)dx

du = - cosec x cot x + cosec² x)dx

du =   cosec²x- cosec x cot x dx

=  ∫ (cosec²x - cosec x cot x) dx /(cosec x - cot x)

=  ∫ du/u

=  ∫ (1/u) du

=  log u + C

=  log (cosec x - cot x) + C

Problem 4 :

Integrate x5 (1 + x6)7

Solution :

Let t = 1 + x⁶

differentiate with respect to x

dt  =  6 x⁵ dx

dt/6  =  x⁵ dx

 x⁵ dx  =  dt/6

=  ∫ x⁵ (1 + x⁶)⁷ dx

=  ∫ t⁷ (dt/6)

=  (1/6) t⁷ dt

=  (1/6) [t(7+1)/(7+1)] + C

=  (1/6) (t8/8) + C

=  (1/48) t8 + C

=  t8/48 + C    

= (1 + x⁶)⁸/48 + C

Problem 5 :

Integrate (2Lx + m)/(Lx² + mx + n)

Solution :

Let t  =  (Lx2+mx+n)

differentiate with respect to x

dt  =  (2Lx + m) dx

=  ∫ (dt/t)

=  log t + C

=  log (Lx² + mx + n) + C

Problem 6 :

Integrate (4ax + 2b)/(ax2 + bx + c)10

Solution :

t  =  ax2+bx+c

differentiate with respect to x

dt  =  2ax+b

= ∫(4ax+2b)/(ax2+bx+c)10 dx

now we are going to take 2 from the numerator

=  ∫ 2 (2ax+2b)/(ax2+bx+c)10 dx

= ∫2 (dt/t10)

=  ∫2 t-10 dt

=  2t(-10+1)/(-10+1) + C

=  2t-9/(-9) + C

=  (-2/9) (ax2 + bx + c)^(-9) + C

=  [-2/9(ax2+bx+c)9] + C

Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here. 

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Angle Bisector Theorem Worksheet

    Jan 26, 22 01:48 AM

    Angle Bisector Theorem Worksheet

    Read More

  2. Angle Bisector Theorem Proof

    Jan 26, 22 12:58 AM

    Angle Bisector Theorem Proof (Internally and Externally) - Step by step explanation

    Read More

  3. How to Find HCF and LCM Easily

    Jan 25, 22 02:08 AM

    How to Find HCF and LCM Easily - Concept - Examples

    Read More